Adsorption of cadmium (II) and zinc (II) on boron enrichment process waste in aqueous solutions: Batch and fixed-bed system studies - Atar, Necip; Olgun, A.; Wang, Shaobin (Elsevier BV, 2012)
Adsorption performance of a waste material from boron enrichment process (BW) in removing zinc (II) and cadmium (II) ions from aqueous solution was studied in batch and fixed bed reactors. The optimum conditions for the treatment process were obtained by observing the influences of solution pH, contact time, initial solution concentration, and adsorbent dosage. The adsorption of the two metal ions showed rapid uptake on the waste in the initial 40 min. Kinetic and equilibrium studies indicated that adsorption of the heavy metal ions from solution follows the sequence of Cd2+ > Zn2+ and the Langmuir adsorption isotherm. The kinetic data were fitted closely to a pseudo-second-order model. Ion exchange between Ca2+ with Cd2+/Zn2+ was found to be the adsorption mechanism. Batch and column tests demonstrated that BW is a highly effective adsorbent for metal ion removal.